Effects of economics and demographics on global fisheries sustainability - Qi Ding; Yali Wang; Xinjun Chen; Yong Chen (Conservation Biology, 2017)
A good understanding of social factors that lead to marine ecological change is important to developing sustainable global fisheries. We used balanced panel models and conducted cross‐national time‐series analyses (1970–2010) of 122 nations to examine how economic prosperity and population growth affected the sustainability of marine ecosystems. We used catches in economic exclusive zone (EEZ); mean trophic level of fishery landings (MTL); primary production required to sustain catches (expressed as percentage of local primary production [%PPR]); and an index of ecosystem overfishing (i.e., the loss in secondary production index [L index]) as indicators of ecological change in marine ecosystems. The EEZ catch, %PPR, and L index declined gradually after gross domestic product (GDP) per capita reached $15,000, $14,000, and $19,000, respectively, and MTL increased steadily once GDP per capita exceeded $20,000. These relationships suggest that economic growth and biodiversity conservation are compatible goals. However, increasing human populations would degrade marine ecosystems. Specifically, a doubling of human population caused an increase in the %PPR of 17.1% and in the L index of 0.0254 and a decline in the MTL of 0.176. A 1% increase in human population resulted in a 0.744% increase in EEZ catch. These results highlight the importance of considering social and economic factors in developing sustainable fisheries management policy.